LABORATORY INVESTIGATION OF SKID RESISTANCE FOR STEEL SLAG UTILIZATION AS CHIP SEAL - Laely Fitria Hidayatiningrum; Latif Budi Suparma (Jurnal Transportasi, 2011)
Slag as waste material of steel-making process has similar characteristics with aggregate that has been widely used in pavement construction. The use of slag as chip seal aggregate to provide skid resistance needs to be analyzed. In this laboratory study, the chip seal samples are made using steel slag and natural aggregate. The bonding materials used are asphalt and epoxy resin. Skid resistance tests for all chip seal samples and also hot rolled sheet pavement without chip seal application are performed using the Portable British Pendulum Tester. The results show the variations of chip seal aggregate weight are inconsistent. The natural aggregate used as chip seal material could produce high skid resistance value of 10.3% higher than that using steel slag. Also the skid resistance of chip seal with the ALD 3 mm are not significantly different with that of ALD 6 mm. Similar results occur on the skid resistance of chip seals using epoxy resin and asphalt.Keywords: steel slag, waste material, chip seal, the Portable British Pendulum Tester, skid resistance.